The effect of the duration of clopidogrel use on hsCRP levels after stenting the target vessel in patients with acute coronary syndrome - Cekici, Y.; Korkmaz, H.; Akbulut, M.; Celik, A. (Oxford Univ Press, 2011)
[Abstract Not Available]